Applied problems of physical education students of economic specialties - O.Y. Dubinskaya; I.A. Salatenko (H.S. Skovoroda Kharkov National Pedagogical University, 2014)
Purpose : to analyze the problems of physical education students of economics in the context of professionally applied physical training. Material : analysis of Ukrainian and foreign publications on species means of improving professional-applied physical training of students in higher education. Results : It was found that the state system of physical education students is ineffective. It does not provide psychophysical and professional readiness of graduates for productive activities and later life. The system also needs constant improvement. A new approach to solving the problem of training to learn the adoption of practical importance of physical education. Also the formation of motivation by demonstrating a real need and usefulness of the proposed exercise. Such exercises should be differentiated, taking into account the health status and subsequent career expectations. Conclusion: it is proved that for an efficient system of training is necessary to use popular among students sports. It is also necessary to take into account the interests of students when choosing tools professionally applied physical training.